Badania preferencji wobec marek - znaczenie w zarządzaniu - Augustyniak, Hanna; Majewska, Maria (Wydział Prawa i Administracji UAM, 1997)
The article is an attempt to create a methodological concept of research of brand-name perception and preferences and a presentation of empirical results of such a research. The objective of the research was to diagnose the level of perception and preference differentiation of selected brand-names of coffee and to identify factors which cause this differentiation. Age, gender and educational background were hypotetically taken as potential factors which may cause the phenomenon. The research took into account prices and other determinants of the preferences. The research employed the method of partial survey. The population of Poznań above 18 was taken as the general population for the research. The survey used representative method based on a study of perceptions and preferences of randomly selected customers of food stores handling coffee. The research evaluated the perception of utility characteristics and consumer behavior as well as attitudes expressed through purchase decision-making process, buying only certain brands of coffee or declaring such a predisposition. The survey indicates substantial consumer preferences differentiation. The penchant to buy two leading brands of coffeee: Jacobs and Astra is very well pronounced. The research indicates that age, education and gender are indeed, the determinants of the surveyed preferences. Notwithstanding, the authors recommend further, sequential research of the same scope to make the study conclusive for management.
The managerial importance of research on brand-name preferences